ACCESSIBLE MALOCA PROJECT: EXPERTISE DEVELOPED IN THE ADAPTATION OF DIDACTIC AND PARADIDACTIC MATERIALS - Nunes Júnior, Wallace Oliveira; Lopes, Lorena Vieira; de Souza, Dalmir Pacheco; Garcia, André Vitor Protázio; de Souza, Luíse Rafaela Costa; Cavalcante, Stepheson De Amorim; Botelho, Wandreow Rogger Queiroz; dos Santos Neto, Jurandir Ferreira; Medeiros, Isabele Verçosa Gomes; Farias, Melissa dos Santos (Seven Editora, 2025)
In the state of Amazonas, approximately 253 thousand people with disabilities (PwD) face barriers to access education, work and leisure, demanding inclusive initiatives. In this context, the Accessible Maloca project, developed by the Federal Institute of Amazonas (IFAM), Manaus Centro campus, emerges as an extension action aimed at adapting didactic and paradidactic materials with accessibility resources such as audio, audio description and Libras, following the principles of universal design. The project is part of the Apoema Assistive Technology Center and has the participation of volunteers, students and servers. This study aims to report the experience of scholarship students involved in the adaptation of materials between August 2023 and April 2024, highlighting the stages of the process and the challenges faced. The research, with a qualitative approach, descriptive and exploratory, used bibliographic and documentary sources. The results contribute to improving accessibility practices and fostering new inclusive actions in the educational field.DOI: https://doi.org/10.56238/sevened2025.018-030